Eksplorasi Dinamika Tren Harga Emas ANTAM LM Menggunakan Pendekatan Least Square: Kajian Algoritma dalam JASP: - - Wahyudi, Hijrah; Mardiyati, Mardiyati (Jurnal Ekonomi STIEP, 2024)
This research aims to analyze the trend of ANTAM LM Gold prices using the least square method through the JASP application and evaluate the reliability of its prediction results. Data on ANTAM LM Gold prices were collected and analyzed using the least square method in the JASP software. The analysis results show that the predicted prices of ANTAM LM Gold can still be trusted, with relatively small and reasonable differences between predicted and actual values. Although the predictions are not always exactly the same as the actual values, the trend analysis can still be relied upon to predict the direction of price movements. An interesting phenomenon is also revealed, namely that the actual selling prices of ANTAM LM Gold tend to decrease from the middle of the month to the beginning of the following month. This information can be used by investors as a guide to buy ANTAM LM Gold when prices are decreasing. In conclusion, the results of the trend analysis of ANTAM LM Gold prices using the least square method through the JASP application provide a significant contribution to more informed and potential investment decision-making.